Annealing of dry etch damage in metallized and bare (-201) Ga2O3 - Yang, Jiancheng; Ren, Fan; Khanna, Rohit; Bevlin, Kristen; Geerpuram, Dwarakanath; Tung, Li-Chun; Lin, Jingyu; Jiang, Hongxing; Lee, Jonathan; Flitsiyan, Elena; Chernyak, Leonid; Pearton, S. J.; et al. (Journal of vacuum science and technology. B, Nanotechnology & microelectronics, 2017)
The surface of single-crystal (-201) oriented β-Ga2O3 was etched in BCl3/Ar inductively coupled plasmas under conditions (an excitation frequency of 13.56 MHz, a source power of 400 W, and a dc self-bias of −450 V) that produce removal rates of ∼700 Å min−1. Annealing at 400 and 450 °C was carried out after etching on Ni/Au Schottky diodes formed on the surface either before or after the annealing step. Current–voltage (I–V) measurements were used to extract the Schottky barrier height (Φ), diode ideality factor (n), and reverse breakdown voltage (VRB) for plasma damaged diodes after annealing. Annealing at 450 °C was found to essentially restore the values of Φ, n, and VRB to their reference (unetched) values on samples metallized after etching and annealing. Thermal annealing at either temperature of metallized diodes degraded their reverse breakdown voltage, showing that Ni/Au is not stable on β-Ga2O3 at these temperatures. Photoluminescence revealed a decrease in total emission intensity in the near band-edge region after the introduction of etch damage. Electron beam-induced current measurements showed a decrease in the minority carrier diffusion length from 350 μm in the control sample to 311 μm in the etched sample.